2020
DOI: 10.1101/2020.05.20.106575
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 targets cortical neurons of 3D human brain organoids and shows neurodegeneration-like effects

Abstract: COVID-19 pandemic caused by SARS-CoV-2 infection is a public health emergency. COVID-19 typically exhibits respiratory illness. Unexpectedly, emerging clinical reports indicate that neurological symptoms continue to rise, suggesting detrimental effects of SARS-CoV-2 on the central nervous system (CNS). Here, we show that a Düsseldorf isolate of SARS-CoV-2 enters 3D human brain organoids within two days of exposure. Using COVID-19 convalescent serum, we identified that SARS-CoV-2 preferably targets soma of cort… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 39 publications
1
33
1
Order By: Relevance
“…Recent reports have similarly explored neurotropism of SARS-CoV-2 using brain organoids and neurospheres, but with contradictory findings to those we observed here (Ramani et al, 2020;Song et al, 2020). One possible explanation is the use of pseudovirus versus live SARS-CoV-2, with other reports making use of live viral isolates.…”
Section: Sars-cov-2 Spike Pseudovirus Only Infects Chp Cells Of Braincontrasting
confidence: 87%
“…Recent reports have similarly explored neurotropism of SARS-CoV-2 using brain organoids and neurospheres, but with contradictory findings to those we observed here (Ramani et al, 2020;Song et al, 2020). One possible explanation is the use of pseudovirus versus live SARS-CoV-2, with other reports making use of live viral isolates.…”
Section: Sars-cov-2 Spike Pseudovirus Only Infects Chp Cells Of Braincontrasting
confidence: 87%
“…Next, we generated hiPSC-derived brain organoids (Amin and Pasca, 2018;Pellegrini et al, 2020;Qian et al, 2016;Velasco et al, 2019) to model the SARS-CoV-2 infection of neuronal cells in 3D. Similar to a recent report (Ramani et al, 2020), we observed infection of neuronal cells in nine-week-old organoids as early as 24 hpi, with significantly increased number of SARS-CoV-2 positive cells at 96 hpi ( Figure 1A-C, Figure S2C). Although the majority of the SARS-CoV-2 infected cells were localized within MAP2 positive cellular fields of mature neurons ( Figure 1B.2, Figure S2C), we also observed infection of SOX2-positive neural stem cells with bipolar morphology and cells localized around the neural tube-like structures ( Figure 1B.1).…”
Section: Modeling Sars-cov-2 Neuroinvasion and Cellular Death Using Hsupporting
confidence: 83%
“…The information currently available is from research on SARS-CoV, which has 78% nucleotide homology with SARS-CoV-2 ( 18 ). Although CNS tropism has been described ( 20 ), no specific models of neural cell lines have been developed for the study of SARS-CoV-2; however, neural progenitor cells (NPCs), neurons and microglia derived from human induced pluripotent stem cells (hIPSCs) have already been used in in vitro studies of SARS-CoV-2 viral infection, demonstrating the virus potential to infect CNS cells ( 116 118 ). Previous studies with other neurotropic human coronaviruses showed possible neural cell lines susceptible to infection by SARS-CoV-2 that may be useful in studying the possible mechanisms by which the virus infects the CNS.…”
Section: Cns Cell Linesmentioning
confidence: 99%
“…Ramani et al ( 116 ) observed that in these brain organoids, the virus mainly infects mature cortical neurons and presents a perinuclear distribution within these cells. Furthermore, neurodegenerative effects have been observed in cells infected by SARS-CoV-2, including cell death and hyperphosphorylation, as well as mislocation of Tau protein; these alterations are observed in such conditions as tauopathies or Alzheimer disease ( 116 ).…”
Section: Brain Organoids As a Model Of Cns Infection By Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation